STUDI NETNOGRAFI PADA AKSI BEAT PLASTIC POLLUTION OLEH UNITED NATIONS ENVIRONMENT DI MEDIA SOSIAL INSTAGRAM - Serra Annisa (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
World Environment Day (WED) is commemorated every June 5 to raise awareness of all people around the world to care about the environment. The theme of the 2018 WED is “Defeating Plastic Pollution”, the action of inviting people around the world to reduce the burden of plastic, one of which is by inviting all parties who use the internet to gather information about this action by uploading it on social media using the hashtag #BeatPlasticPollution. The purpose of this study was to analyze the content of the Action to Beat Plastic Pollution. This study uses a netnographic method and data collection is done through online observation. The results of this study provide an overview of the uploaded content, namely the use of visuals in the format of photos, designs or videos, how to deliver messages, the level of involvement, and the involvement of environmental activists and celebrities participating in the Defeating Plastic Pollution action. The UN Environment has made a decision using Instagram as a media to take action to defeat plastic pollution. The substance of this research is policy for social media and for local people to get Instagram content on social media that has a high level of involvement.